Reliability, validity, and measurement invariance of a Chinese handwriting legibility scale among primary students in central China - Lu, Hong; Chen, Xin; Leung, Frederick K. S.; Zuo, Haode (Frontiers in Psychology, 2023)
Background Chinese handwriting has a close relationship with spatial cognition, and the legibility dimension is prominent with its spatial-oriented characteristics. However, handwriting evaluation focusing on the detailed spatial aspects of the legibility dimension in the Chinese context is rare. Aims and methods We aimed to develop a Chinese Handwriting Legibility Scale (CHLS) and examine its reliability, validity, and measurement invariance among Chinese primary students of different grades. A total of 684 students aged 8–12 years were recruited from a mainstream primary school in central China and were asked to copy a Chinese template as legibly as possible within 4 min. The developed CHLS was used to assess these students’ legibility performance. Results The seven-criteria CHLS favored content validity. The inter-rater reliability was good; however, the scoring instructions need to be refined. Principal component analysis (PCA) revealed a one-factor solution explaining 62.336% of the variance of the seven-criteria CHLS, and confirmatory factor analysis (CFA) confirmed its appropriateness. There was a high internal consistency (α = 0.902). In terms of measurement invariance, the factor structures and loadings of the CHLS were consistent across students of different grades; however, significant intercept variations were detected between students of Grades 2 and 4. Conclusion CHLS may be effective for evaluating Chinese handwriting legibility performance in the Chinese primary school context in the central region. Students’ Chinese handwriting legibility performance may have developmental specificity in different grades.